Evaluating the immunogenicity of heparin and heparin derivatives by measuring their binding to platelet factor 4 using biolayer interferometry - Chen, Qingqing; Li, Fei; Wang, Haoran; Bu, Changkai; Shi, Feng; Jin, Lan; Zhang, Qunye; Chi, Lianli (Frontiers in Molecular Biosciences, 2022)
Heparin (HP) is a polysaccharide that is widely used in the clinic as an anticoagulant. A major side effect associated with HP is the heparin-induced thrombocytopenia (HIT), which is initiated by the immune response to complex formed by HP and platelet factor 4 (PF4). Low molecular weight heparins (LMWHs) are the depolymerized version of HP, which have reduced risks of inducing HIT. However, it is still necessary to evaluate the immunogenicity of LMWHs to ensure their drug safety. Since HIT involves very complicated processes, the evaluation of HP and LMWH immunogenicity requires experiments from multiple aspects, of which the binding affinity between HP and PF4 is a key property to be monitored. Herein, we developed a novel competitive biolayer interferometry (BLI) method to investigate the binding affinity between HP and PF4. The influence of different domains in HP on its immunogenicity was compared for better understanding of the molecular mechanism of HP immunogenicity. Furthermore, the half maximal inhibitory concentration (IC50) of HP and LMWH can be measured by competitive combination, which is important for the quality control during the developing and manufacturing of HP and LMWH drugs.